2005
DOI: 10.1124/dmd.104.002519
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPORT OF THE DOPAMINE D2 AGONIST PRAMIPEXOLE BY RAT ORGANIC CATION TRANSPORTERS OCT1 AND OCT2 IN KIDNEY

Abstract: ABSTRACT:We investigated the mechanism of renal tubular secretion of the dopamine D 2 receptor agonist pramipexole in rats, focusing on organic cation transporters 1 and 2. The uptake of [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 34 publications
0
36
1
Order By: Relevance
“…Table 2 shows the affinity for hMATE1, hMATE2-K, and OCT2 of various compounds excreted from the kidney. K m values of hOCT2 and rat (r) OCT2 were cited from previous papers (Urakami et al, 2001;Ishiguro et al, 2005;Koepsell et al, 2007). Most drugs showed higher affinity for OCT2 than for hMATEs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the affinity for hMATE1, hMATE2-K, and OCT2 of various compounds excreted from the kidney. K m values of hOCT2 and rat (r) OCT2 were cited from previous papers (Urakami et al, 2001;Ishiguro et al, 2005;Koepsell et al, 2007). Most drugs showed higher affinity for OCT2 than for hMATEs.…”
Section: Resultsmentioning
confidence: 99%
“…3; Table 1). It has been reported that pramipexole is transported by rOCT1 and rOCT2 (Ishiguro et al, 2005), but it is unclear whether pramipexole is transported by the hMATE family and hOCT2. Pramipexole may be a good probe to distinguish the molecular mechanisms by which the hMATE family recognizes substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, Oct1 is expressed in the liver, kidney, and small intestine (Grü ndemann et al, 1994). Oct2 has a substrate specificity similar to that of Oct1, but is predominantly expressed in the kidney, as is the case in humans (Grü ndemann et al, 1998, Ishiguro et al, 2005. In addition, it was reported that Oct1 gene-knockout mice showed greatly reduced hepatic uptake and direct intestinal excretion of Oct1 substrates, indicating that this transporter plays an essential role in the disposition of organic cations in the liver and intestine (Jonker et al, 2001;Wang et al, 2002).…”
mentioning
confidence: 99%
“…Male Wistar rats (7 or 8 weeks; Sankyo Co.) were housed three per cage with free access to commercial chow and tap water and maintained on a 12-h dark/ light cycle (8:00 AM-8:00 PM light) in an air-controlled room (temperature, 24.5 Ϯ 1°C; humidity, 55 Ϯ 5%). Uptake studies using kidney slices were carried out as described in a previous report (Ishiguro et al, 2005). Kidney slices (0.3 mm in thickness) from rats were put in ice-cold oxygenated incubation buffer.…”
Section: Methodsmentioning
confidence: 99%